Sharing Knowledge within Supply Chains: A Conceptual Model Using the Theories - Rossella Canestrino; Saeed Khayat Moghadam; Abolfazl Danaei; leila oliaee (International Journal of Supply Chain Management, 2020)
Abstract. This paper aims to identify the factors influencing knowledge sharing in the supply chain and the related theories. A quali-quantitative mixed method has been adopted in our exploratory study. Firstly, a Delphi method has been applied to design the conceptual model. After this, the resulting model has been examined and empirically applied to explore the selected case study, by a quantitative approach. The main instrument of the study is a re-searcher-made questionnaire that its validity was achieved through Content. Also, Cronbach's alpha test has been used to assess reliability of the questionnaire, which according to the alpha obtained at 93 %, it could be concluded that the questionnaire's reliability is acceptable. Based on the results, an appropriate model for knowledge sharing in supply chain has been developed on the basis of 15 factors and the related theories. The research’s results (arising by the testing and validation of the model) showed that the heterogeneity of knowledge management systems (KMSs) of organizations involved in Khorasan Electricity Supply Chain, Iran is above average level. Trust among enterprises in supply chain and the clear economic benefits are at average level. This paper will contribute to improve understanding on the factors influencing KS among organizations involved in supply chain, providing for a conceptual model useful for future investigations. Keywords: Knowledge Sharing, Supply Chain, Heterogeneous KMSs, Inter-organizational Trust